Residential satisfaction and social integration in public low cost housing in Malaysia - Hashim, Ahmad Hariza (Universiti Putra Malaysia Press, 2003)
The research examined the relationship between social integration and residential satisfaction of residents in low cost housing in Malaysia. Two urban and non-urban areas in Selangor were chosen for this study involving 472 respondents. 58% of the respondents are Malay, 22% Chinese and 20% Indians. It was shown that residents with strong residential attachments and high levels of satisfaction are actively involved in the community activities held in their neighbourhood. It was also found that factors such as default in the physical structures of the house and poor social and physical environments could affect the social integration in the neighbourhood. Therefore properly planned residential projects with attention given towards residential satisfaction need to be considered because they can help foster the process of socializing people into communities.